Implementasi Tata Kelola Pemerintahan yang Baik Melalui Transformasi Digital dan Kerja Sama Antar Lembaga : Strategi Menuju Indonesia Emas 2045 - Hartati Malkab; Khair Khalis Syurkati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The era of digital transformation and the Indonesia Golden 2045 agenda demands a new paradigm in governance that prioritises inter-institutional collaboration to achieve effective and responsive governance. This transformation has been accelerated by the implementation of the Electronic-Based Government SIstem (SPBE) and the enactment of Law No. 1 of 2024 concerning Information and Electronic Transactions (ITE). This study analyses the implementation of good governance through digital transformation and inter-institutional collaboration, evaluates the challenges and opportunities in the digital era, and formulates optimisation strategies to support the achievement of Indonesia's Golden 2045. The research employs a normative juridical method, incorporating both conceptual and statutory approaches, and is reinforced by a systematic literature review analysis of current regulations and case studies of SPBE implementation in various regions across Indonesia. Data were collected through documentary studies of 35 laws and regulations and analysis of 40 academic literature sources from the period 2020-2025. The implementation of good governance through digital transformation shows positive results with SPBE success at the regional level, a 28% increase in government effectiveness, and the development of integrated service platforms serving 72 million transactions annually. However, challenges remain in regulatory harmonisation (47% overlapping authorities), digital capacity gaps (34% of institutions not yet optimal), and sectoral culture among institutions. Inter-institutional collaboration through digital transformation demonstrates positive trends in realizing good governance, but requires strengthening of digital legal frameworks, development of technological infrastructure, and organizational culture transformation to support the achievement of the Indonesia Golden 2045 vision.